Bermain Sambil Belajar: Strategi Pengenalan Bahasa Inggris untuk Balita di Klinik Fina Sembiring Kecamatan Medan Polonia Tahun 2024 - Rudi Purwana; Mariana Mariana; Asrul Asrul; Riani Baiduri Siregar; Heri Saputra; Hendri Irawan (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This Community Service aims to introduce English to toddlers at Fina Sembiring Clinic, Medan Polonia District, through a play-based learning approach in 2024. The program utilizes interactive teaching methods that combine educational games, children's songs, and picture stories to create a fun and effective learning environment for the children. By using this strategy, it is expected that children can develop basic English skills, such as vocabulary, pronunciation, and basic comprehension through age-appropriate activities. Active parental participation is also a focus of this program, providing guidelines and brief training to help them continue practicing English at home. The effectiveness of the program is evaluated through direct observation, interviews with parents, and language development tests specifically designed for toddlers. The results of this activity show that the play-based learning approach can increase children's interest and basic English skills. Moreover, active parental involvement proves crucial in supporting the success of this program. In conclusion, this approach not only improves toddlers' English skills but also creates a positive bond between children and parents in the learning process.